Compartmented Fluidized Bed Gasifier For Syngas and Power Generation Using Biomass?, : - Chok, Vui; Wee, Siaw; Gorin, Alexander; Chua, Han (Info not available, 2008)
The present paper addresses the development of a new indirectly heated gasification technology, Compartmented Fluidized Bed Gasification (CFBG) that uses air and steam as gasification agents, for utilizing palm wastes (palm shell) for the production of high-energy syngas (calorific-value of gas is around 15-17 MJ/Nm3), which can be used for power generation and chemical processes. CFBG is a single compartmented reactor, which incorporates two sets of v-valves and risers to control the circulating solids across the two compartments for heat transfer, yet without nitrogen contamination. A 0.5 tones per day (TPD) CFBG pilot plant, with reactor height and ID of 3.10 m and 0.66 m respectively has been constructed most recently. The primary aim of this paper to describe the first hand operational performance of CFBG pilot plant, specifically its solid circulation rate (SCR) relationship with respect to 4 independent operating parameters namely bed height, aeration rate for main bed, v-valve and riser, configured based on 24 full factorial design of experiment. The SCR is statistically analyzed using Yates? method and analysis of variance (ANOVA). Half normal plot is also presented to indicate the most important effects..